Dilema Penggunaan Forensik Digital dalam Penanganan Tindak Pidana di Bidang Perpajakan Pasca Putusan MK No 83/PUU-XXI/2023 - Febrian Halomoan; Handar Subhandi Bakhtiar (CV. Era Digital Nusantara, 2025)
This article examines the constitutional implications of the Indonesian Constitutional Court Decision No. 83/PUU-XXI/2023 on the use of digital forensics in criminal tax enforcement. The decision restricts the preliminary evidence examination under Law No. 7 of 2021 on Tax Harmonization by prohibiting coercive measures, thereby creating significant legal dilemmas for the Directorate General of Taxes (DGT) in investigating tax crimes classified as white-collar offenses. The legal challenge emerges from the temporal and evidentiary vulnerability of digital evidence, which requires immediate acquisition during preliminary examination to maintain data integrity and admissibility. Unlike traditional evidence, digital data can be readily altered, deleted, or manipulated if acquisition is delayed until the investigation phase. The Court's restrictive interpretation of preliminary examination authority consequently diminishes the DGT's practical capacity to employ digital forensic techniques essential for uncovering sophisticated tax evasion schemes, particularly those involving aggressive tax planning and Base Erosion and Profit Shifting (BEPS) strategies. The article employs normative legal research methodology with statutory and conceptual approaches to analyze the decision's impact on tax crime enforcement effectiveness. Findings indicate that post-constitutional interpretation, the DGT's usage of digital forensic investigation has declined substantially, with investigating officers (PPNS) hesitant to utilize these methodologies due to heightened vulnerability to pre-trial objections regarding alleged coercive conduct. The study recommends explicit statutory codification of digital forensic activities within the framework of preliminary examination to clarify their legitimacy, protect investigating officers from legal challenge, and maintain the efficacy of tax law enforcement while respecting constitutional protections.